Beyond Modernity′s Meanings: Engaging the Postmodern in Cultural Anthropology - Coombe, Rosemary J. (Culture, 1991)
Drawing upon literature in cultural studies, the author argues that the concept of the postmodern challenges the discipline of cultural anthropology in a number of ways. Interpretive anthropology is a modernist enterprise — one with untenable premises and limitations that are increasingly evident in the condition of postmodernity. Exploring the intersections between culture and power in local contexts, cultural anthropologists engage the postmodern by investigating the cultural politics of everyday life.